Financial Crisis and Sticky Expectations - Saten Kumar; Barrett Owen (Auckland University of Technology (AUT), Faculty of Business, Economics and Law, 2013)
We utilize the Kalman filter and instrumental variable methods to estimate consumption growth persistence for the U.S. Results show that prior to the financial crisis, the stickiness parameter beta was around 0.7. However, when the sample is extended until 2009.Q1, the estimates of beta declined to around 0.5. Extending the sample beyond 2009.Q1 show mild increase in beta. Our findings imply that during the crisis consumers' attentiveness to aggregate information has slightly increased, thereby reducing the persistence of aggregate consumption growth.
Keywords: C5; E2; 330; financial crisis; Kalman filter; sticky expectations